10Be and 26Al exposure history of the highest mountains in Wales: Evidence from Yr Wyddfa (Snowdon) and Y Glyderau for a nunatak landscape at the global Last Glacial Maximum. (15th June 2022) - Hughes, Philip D.; Glasser, Neil F.; Fink, David
Abstract: Twelve 10 Be and five 26 Al samples from the mountains of Yr Wyddfa (Snowdon) (1085 m) (n = 7 10 Be) and Y Glyderau (the Glyders) (1001 m) (n = 5 paired 10 Be/ 26 Al) in Wales provide new insights into landscape evolution in the highest mountains in the British Isles outside of Scotland. The summits of Y Glyderau are characterised by intensely modified frost-shattered surfaces and have long been recognised as exemplars of mountain summit periglacial activity in the British Isles. However, glacially transported boulders on the highest ground indicate that ice overran the summits. Bedrock and boulder surfaces at altitudes >900 m yield 10 Be and 26 Al exposure ages of 61–78 ka, indicating that the last Welsh Ice Cap did not override and erode Y Glyderau summits at the global Last Glacial Maximum (LGM) and the summits stood as nunataks. Both the geomorphological and the exposure dating evidence indicate ice overran the summits earlier in the last glacial cycle during MIS 4, although erosion was only partial. Thick ice over Wales at this time is consistent with evidence of an extensive British-Irish Ice Sheet that reached the continental shelf to the west in MIS 4. The ice-scoured lower slopes of Y Glyderau and the arêtes of Yr Wyddfa were exposed as the ice cap rapidly thinned between 20-16 ka marking a transition from ice cap to alpine-style glaciation. On Yr Wyddfa, the highest mountain in southern Britain, local ice breached and abraded the central parts of the Crib Goch-Crib y Ddysgl arête as high as 874 m until c. 16 ka. However, some arête crests yielded Holocene ages (4.4–9.3 ka), which reflect continual post-glacial stripping. Highlights: 10 Be/ 26 Al dating provides new insights into the history of glaciation over Wales. The Welsh Ice Cap was last thickest in MIS 4 when ice submerged the highest peaks. Ice was thinner at the global LGM when the highest summits existed as nunataks. By 17-15 ka the ice cap had thinned forming localised alpine-style valley glaciers. Arête rock surfaces have continued to erode by 1–2 m since deglaciation.